2015
DOI: 10.3923/ijzr.2015.198.206
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metal Pollution and Fish Parasites as Biological Indicators at Arabian Gulf off Dammam Coast, Saudi Arabia

Abstract: A new approach is chosen to visualize ecosystem health by using parasite bioindicators in Arabian Gulf off Dammam cost. Three hundred and sixty fish specimens belonging to three species of fish were examined parasitological for external and internal metazoan parasites. The seasonal prevalence of the detected parasites was differing from season to another. The highest rate occurred in summer and spring while, the lowest rate was in autumn and winter, respectively. The obtained data showed that Monogeneans preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…The majority of fish serve as an intermediate host for many parasites, which reduces the food value of fish and causes mass mortality [90]. Bayoumy et al [91] concluded that several species of parasite, including metazoan parasite, crustaceans, digenean, and Monogenea were detected in different tissues of Nile tilapia fish. Monogenea showed highly antagonistic action with chromium, iron, and nickel.…”
Section: Relationship Between Heavy Metals Pollution and Parasite Infestation In Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of fish serve as an intermediate host for many parasites, which reduces the food value of fish and causes mass mortality [90]. Bayoumy et al [91] concluded that several species of parasite, including metazoan parasite, crustaceans, digenean, and Monogenea were detected in different tissues of Nile tilapia fish. Monogenea showed highly antagonistic action with chromium, iron, and nickel.…”
Section: Relationship Between Heavy Metals Pollution and Parasite Infestation In Fishmentioning
confidence: 99%
“…Meanwhile, the crustacean parasites showed the highest significant positive correlation with zinc and selenium. In another investigation, Bayoumy et al [91] isolated external and internal metazoan parasites from three fish species in the Arabian Gulf of Dammam coast in different environmental weather. The rate of parasitism was higher in spring and summer in comparison to the winter season.…”
Section: Relationship Between Heavy Metals Pollution and Parasite Infestation In Fishmentioning
confidence: 99%
“…Біомоніторин-гу важких металів в органах і тканинах риб присвячено праці Le et al (2016) та Javed & Usmani (2016). Доступні літературні дані свідчать також і про акумуляцію важких металів паразитами риб, що локалізуються в її різних органах (Nachev et al, 2010;Bayoumy et al, 2015;Hassan et al, 2016). Автори доводять, що паразити здатні накопичувати важкі метали в концентраціях, які у багато разів вищі, ніж у тканинах господаря (Sures, 2004;Leite et al, 2017;Sures et al, 2017).…”
Section: вступunclassified
“…The diversity of the parasite/host relationship is the result of adaptive processes to the parasitic lifestyle in different types of hosts, sites, and environments. Numerically there are more species of parasites than any other taxon on the planet (Mackenzie, 1999;Bayoumy et al, 2015). Environmental changes can lead to significant changes in species diversity, prevalence, intensity of infestation and parasitic abundance (Mackenzie, 1999).…”
Section: Introductionmentioning
confidence: 99%